Growth, Physiological, and Intestinal Responses of Low-Weight Day-Old Broiler Chicks to Dietary Infertile Egg Powder - Handayani, F. R.; Widiastuti, E.; Agusetyaningsih, I.; Yudiarti, T.; Sari, D. A. P.; Sugiharto, (Tropical Animal Science Journal, 2025)
The present study examined the consequences of supplementing the diets of low-weight day-old broiler chicks (DOC) with 4% infertile egg powder (IEP). The chicks were categorized into three groups namely; normal-weight DOC, low-weight DOC on a basal diet, and low-weight DOC on a diet that contained 4% IEP (T2). In hematological analysis, there was increase in hemoglobin levels, and mean corpuscular hemoglobin concentration (MCHC) compared to T2, but the MCV was less than T0 (p